2008
DOI: 10.1111/j.1750-3639.2008.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflicted Traumatic Brain Injury in Infants and Young Children

Abstract: This article will discuss the subject of inflicted or abusive head injury in infants and young children. Inflicted neurotrauma is a very common injury and a frequent problem in attempting to distinguish between inflicted and accidental injury. Inflicted head injury occurs usually in the home in the presence of the individual who has inflicted the injury outside the view of unbiased witnesses. Distinguishing between inflicted and accidental injury may be dependent upon the pathological findings and consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 74 publications
2
53
1
Order By: Relevance
“…Subarachnoid hemorrhages and hypoxic ischemic injury are also commonly seen [22,23]. It has been postulated that hypoxic-ischemic injury with iTBI may be related to apnea from traumatic injury to the brainstem or rotational acceleration-deceleration forces causing deep focal injuries that might contribute directly to cardiorespiratory compromise [24].…”
Section: How Is Tbi Different In Children?mentioning
confidence: 99%
“…Subarachnoid hemorrhages and hypoxic ischemic injury are also commonly seen [22,23]. It has been postulated that hypoxic-ischemic injury with iTBI may be related to apnea from traumatic injury to the brainstem or rotational acceleration-deceleration forces causing deep focal injuries that might contribute directly to cardiorespiratory compromise [24].…”
Section: How Is Tbi Different In Children?mentioning
confidence: 99%
“…Liquid remnants of the acute SDH or CSF might then pass into that opened space by effusion from surrounding vessels or even the subarachnoid space, forming the SDHy. 50,52 It should be noticed that in this approach, the SDHy is considered as a consequence of the SDH but not as a directly transformed remnant of it. Alternatively, Mack et al 36 suggested that CSF could physiologically move from the subarachnoid space into interstitial spaces of the dura mater and subsequently via the dural venous plexus into the dural sinuses.…”
Section: Concept 1: Delayed Formation Of Subdural Hygromasmentioning
confidence: 99%
“…If the decreased intracranial pressure that had led to SDHy formation continues, the SDHy may expand. 50,52 This can enlarge the intradural cleavage (ϭ subdural space filled with SDHy) up to the opposite brain side opening a subdural space even above the falx cerebri. Accordingly, SDHys were frequently observed not to be restricted to the brain side of the "original pathology" (eg, acute SDH).…”
Section: Differential Diagnoses Of Subdural Hygromasmentioning
confidence: 99%
See 2 more Smart Citations